Knowledge and attitude on emergency contraception among adolescent students of an urban school (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Emergency contraception (EC) is used to prevent pregnancy in the first 5 days after sexual intercourse, mainly unprotected intercourse, contraceptive failure, rape or coerced unprotected sex. This study aims to identify the knowledge and attitude on EC and associated factors among adolescent students.Method: A cross-sectional study was conducted to find out knowledge and attitude on EC among adolescent students of both sex, grade 11 and 12 at Advanced Academy, a private school in Kumaripati, Lalitpur, Nepal, during 19 January 2018 to 13 February 2018. Non probability convenience sampling and self-administered questionnaire was used for data collection. Association of demographic variables with knowledge and attitude of EC and further correlation between knowledge and attitude were analysed. The SPSS 16 was used for data analysis.Result: Out of 343 students, 211 (61.5%) had fair knowledge of EC, 125 (36.5%) poor and 7 (2%) good knowledge. Favourable attitude towards EC was found in 285 (83.1%) and unfavourable in 58 (16.9%). The mean age was 17.33 ± 0.98 years, 206 (60.1%) in 15-17 year age group (middle adolescence), female 143 (41.7%), and 160 (46.7%) from within Kathmandu valley. There was significant positive co-relation between knowledge and attitude and no significant association between demographic variables with knowledge and attitude.Conclusion: Majority of adolescence students 15-21 years of age had favourable attitude but less knowledgeable in regard to emergency contraception.